AKTIVITAS LACTOBACILLUS PLANTARUM ISOLAT AIR SUSU IBU PADA TIKUS GALUR WISTAR DIABETES MELLITUS - Kartikasari, Oktavia; Astuti, Anggun Dian; Wabula, Mega Berkah Mustika; Dewi, Sri Sinto (Politeknik Kesehatan Tanjung Karang, 2019)
Lactobacillus plantarum is a Lactic Acid Bacteria (LAB) that has the potential to be used as a probiotic agent. Probiotics are antidiabetic because they can inhibit alpha-glucosidase enzymes. This study aims to was to determine the antidiabetic effects of probiotic Lactobacillus plantarum isolates of breast milk (ASI). The study was conducted at the Microbiology Laboratory of the University of Muhammadiyah Semarang and the Pharmacology Laboratory of the Semarang College of Pharmacy during the month of April-June. Experimental research with 25 male wistar mice was divided into 5 groups (K-, K+, P1, P2, P3) Alloxan monohydrate induction was carried out intraperitoneally at a dose of 150mg/kg BW. Fasting blood glucose measurements were performed at baseline (before alloxan induction), post alloxan and at the end of treatment. Diabetic mice fasting blood glucose levels shouldbe± 200 mg/dL. Suspension of Lactobacillus plantarum isolate ASI was carried out orally for 7 days. Based on the ANOVA test there were significant differences in the decrease in blood glucose with a significant value of p-value=0,009<0,05. Based on the Tuckey post hoc test treatment group P1, P2, P3 there were no significant differences between treatment groups even though the dosage was different. 1 time a day treatment is an efficient dose in reducing blood glucose.